Quantum distributed deep learning architectures: Models, discussions, and applications - Kwak, Yunseok; Yun, Won Joon; Kim, Jae Pyoung; Cho, Hyunhee; Park, Jihong; Choi, Minseok; Jung, Soyi; Kim, Joongheon (ICT Express, 2023)
Although deep learning (DL) has already become a state-of-the-art technology for various data processing tasks, data security and computational overload problems often arise due to their high data and computational power dependency. To solve this problem, quantum deep learning (QDL) and distributed deep learning (DDL) has emerged to complement existing DL methods. Furthermore, a quantum distributed deep learning (QDDL) technique that combines and maximizes these advantages is getting attention. This paper compares several model structures for QDDL and discusses their possibilities and limitations to leverage QDDL for some representative application scenarios.
Keywords: Distributed deep learning; Quantum deep learning; Quantum secure communication